Automotive system safety : critical considerations for engineering and effective management - Miller, Joseph (Joseph D.) (Wiley series in quality & reliability engineering, 2020)
"The book serves as a practical guide to incorporate system safety efficiently into an organization. The content is based on the author's experience and can aid small and large automotive companies, and the managers and engineers in those companies, to improve system safety. Further, it will be a useful tool for marketing, sales, and business development professionals to understand and converse knowledgeably with customers and prospects"--